Pendampingan Gemari dan Redarkum Melalui Diseminasi “Stop Pernikahan Dini” - Lila Pangestu Hadiningrum; Diana Zuhroh; Fairuz Sabiq (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
Indonesia is faced with increasing cases of early marriage globally. It is necessary to socialize the minimum age limit and the maturity of the marriage age as an insight to the community and awareness to teenagers so that in planning a family by considering various aspects related to married life. This study raises the priority issues used related to the lack of literacy related to the Marriage Age Limit in Pucang Miliran Village, Tulung, Klaten. Assistance for gemari and redarkum through the dissemination of